The first interactive science museum in Peru: the origin and creation of TECNO-ITINTEC, 1975-1979 - Alejandra Ruiz-León (História, Ciências, Saúde: Manguinhos)
This paper examines the development of the TECNO-ITINTEC museum, the first interactive science museum in Peru, which opened in 1979. The museum functioned under the Institute of Industrial Technology Research and Technical Standards (ITINTEC), a public institution established during the government of Velazco Alvarado. In 1975, Jorge Heraud became the president of ITINTEC’s Board of Directors and proposed a science museum to inspire future generations of scientists. José Castro Mendívil joined as the exhibition’s director and designer. Their motivation to open a museum coincided with the government’s ideals for modernization and nationalization. This article analyzes various sources including newspapers, laws that regulated the institute, reports, and interviews with people involved in the museum to understand how science and politics intersected in TECNO-ITINTEC